2009
DOI: 10.1016/j.bandl.2008.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Relative influence of musical and linguistic experience on early cortical processing of pitch contours

Abstract: To assess domain specificity of experience-dependent pitch representation we evaluated the mismatch negativity (MMN) and discrimination judgments of English musicians, English nonmusicians, and native Chinese for pitch contours presented in a nonspeech context using a passive oddball paradigm. Stimuli consisted of homologues of Mandarin high rising (T2) and high level (T1) tones, and a linear rising ramp (T2L). One condition involved a between-category contrast (T1/T2), the other, a within-category contrast (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
122
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(137 citation statements)
references
References 51 publications
(62 reference statements)
15
122
0
Order By: Relevance
“…Moreover, in order to respond quickly to certain stimuli (facilitated attention), the stimuli with the same or similar characteristics might be detected by interceptive awareness [Michalowski et al, 2015]. Previous studies focusing on tone and color perception have shown that intercategorical stimuli evoke a stronger MMN than intracategorical stimuli [Chandrasekaran et al, 2009;Xi et al, 2010;Mo et al, 2011]. In line with these findings, we suspect that there was a category effect in the present study.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, in order to respond quickly to certain stimuli (facilitated attention), the stimuli with the same or similar characteristics might be detected by interceptive awareness [Michalowski et al, 2015]. Previous studies focusing on tone and color perception have shown that intercategorical stimuli evoke a stronger MMN than intracategorical stimuli [Chandrasekaran et al, 2009;Xi et al, 2010;Mo et al, 2011]. In line with these findings, we suspect that there was a category effect in the present study.…”
Section: Discussionsupporting
confidence: 80%
“…The superior performance of musicians in the FM conditions is in agreement with past work showing a beneficial effect of musical training on discrimination of monotonic pitch contours (Chandrasekaran et al, 2009;Bidelman et al, 2011) and detection of a single incongruity in the fundamental-frequency contour of a spoken phrase (Deguchi et al, 2012). The fluctuation of the stochastic FM of the current work is nonmonotonic, extending past findings to more complex pattern discrimination.…”
Section: Discussionsupporting
confidence: 79%
“…Indeed, native listeners of Mandarin Chinese show enhanced MMNs in response to changes in linguistic pitch patterns (Chandrasekaran et al, 2007(Chandrasekaran et al, , 2009a with stronger responses over the right compared to left hemisphere (Luo et al, 2006;Ren et al, 2009). These studies demonstrate that early cortical pitch processing for isolated tones, as indexed by the MMN, is heightened by linguistic pitch experience (i.e., languages which use pitch to signal word meaning).…”
Section: Introductionmentioning
confidence: 98%